Effectiveness of Cognitive-behavioral Therapy and Mental Imagery Exercises on Health-related Quality of Life of Patients With Leukemia and Lymphoma - Abbas Betiar; Naser Saraj Khorrami; Behnam Makvandi (Iran University of Medical Sciences, 2022)
Background: Patients with cancer experience considerable psychological distress, which leads to depressive symptoms, severe anxiety, and decreased quality of life. The present study aimed to determine the effectiveness of Cognitive-Behavioral Therapy (CBT) and Mental Imagery Exercises (MIE) on the Health-Related Quality of Life (HRQoL) of patients with leukemia and lymphoma living in Babol City, Iran. Methods: This research was a field trial study with a pre-test, post-test design and a control group. The statistical population consisted of all male and female patients with leukemia and lymphoma, referring to the Hematology Department of Ayatollah Rouhani Hospital of Babol Province, in 2019. A total of 45 patients were recruited based on the inclusion criteria and were randomly assigned into two experimental groups and one control group (15 per group). The first experimental group received eight 90-minute sessions of individual CBT and the second experimental group received ten 90-minute sessions of MIE. The control group received no intervention. The study data were collected by the 36-item short-form survey (SF-36) before and 45 days after the last treatment session. Then, the data were analyzed using descriptive (mean, standard deviation) and inferential statistics (analysis of covariance [ANCOVA]) in SPSS software, v. 23.  Results: The results indicated that CBT and MIE had a significant positive effect on HRQoL in patients with leukemia and lymphoma (P<0.001). There was no significant difference between the effectiveness of the two therapies.  Conclusion: Considering the effectiveness of the CBT and MIE on HRQoL in patients with cancer, we suggest they be utilized extensively along with medical and clinical interventions to improve the HRQoL of cancer patients.